The First Crested Duck Genome Reveals Clues to Genetic Compensation and Crest Cushion Formation - Guobin Chang; Xiaoya Yuan; Qixin Guo; Hao Bai; Xiaofang Cao; Meng Liu; Zhixiu Wang; Bichun Li; Shasha Wang; Yong Jiang; Zhiquan Wang; Yang Zhang; et al. (Genomics, Proteomics & Bioinformatics, 2023)
The Chinese crested (CC) duck is a unique indigenous waterfowl breed, which has a crest cushion that affects its survival rate. Therefore, the CC duck is an ideal model to investigate the genetic compensation response to maintain genetic stability. In the present study, we first generated a chromosome-level genome of CC ducks. Comparative genomics revealed that genes related to tissue repair, immune function, and tumors were under strong positive selection, indicating that these adaptive changes might enhance cancer resistance and immune response to maintain the genetic stability of CC ducks. We also assembled a Chinese spot-billed (Csp-b) duck genome, and detected the structural variations (SVs) in the genome assemblies of three ducks (i.e., CC duck, Csp-b duck, and Peking duck). Functional analysis revealed that several SVs were related to the immune system of CC ducks, further strongly suggesting that genetic compensation in the anti-tumor and immune systems supports the survival of CC ducks. Moreover, we confirmed that the CC duck originated from the mallard ducks. Finally, we revealed the physiological and genetic basis of crest traits and identified a causative mutation in TAS2R40 that leads to crest formation. Overall, the findings of this study provide new insights into the role of genetic compensation in adaptive evolution.